posted by deborah .
x+1 -x+2 = x+3
____ _____ ____
2 3 4
How do I solve this equations? These are fractions
mi don't know
I'm going to assume your problem is this:
(x+1)/2 - (x+2)/3 = (x+3)/4
...and you are trying to solve for x.
If so, here's how you would go about it:
First, get rid of the fractions. Let's multiply every term by 12.
12 [(x+1)/2 - (x+2)/3 = (x+3)/4]
6(x+1) - 4(x+2) = 3(x+3)
This is now easier to solve for x.
Working this out:
6x + 6 - 4x - 8 = 3x + 9
2x - 2 = 3x + 9
-11 = x
Substitute -11 for x in the original equation to check. It always helps to check your work!
I hope this helps and is what you were asking.